Quizizz Application and understanding texts in English texts with the content of “Aprendo en Casa” Educational Platform - Laura, Kevin (2021)
The objective of this research was to determine the results of the level of understanding texts in English with the content of “Aprendo en Casa” Educational Platform in second grade students at a Public School in Tacna by using Quizizz, 2020. The type of research that was used is experimental and the form was pre-experimental, the research method is hypothetico-deductive. The procedure for obtaining the data was through the application of pre and post-tests. The results indicate that after the post-test, 68.75% of students reached an outstanding level of achievement, 31.25% are at the expected level of achievement, 0% are at the process level, and at the beginning level. From the results obtained, it can be stated that the students from second grade managed to improve their level of understanding of English texts with the content of “Aprendo en Casa” Educational Platform through Quizizz.